A genetically targeted optical sensor to monitor calcium signals in astrocyte processes - Shigetomi, Eiji (2010)
Calcium signaling is studied as a potential form of astrocyte excitability that may control astrocyte involvement in synaptic and cerebrovascular regulation. Fundamental questions remain unanswered about astrocyte calcium signaling, as current methods can not resolve calcium in small volume compartments, such as near the cell membrane and in distal cell processes. We modified the genetically encoded calcium sensor GCaMP2 with a membrane-tethering domain, Lck, increasing the level of Lck-GCaMP2 near the plasma membrane tenfold as compared with conventional GCaMP2. Using Lck-GCaMP2 in rat hippocampal astrocyte-neuron cocultures, we measured near-membrane calcium signals that were evoked pharmacologically or by single action potential–mediated neurotransmitter release. Moreover, we identified highly localized and frequent spontaneous calcium signals in astrocyte somata and processes that conventional GCaMP2 failed to detect. Lck-GCaMP2 acts as a genetically targeted calcium sensor for monitoring calcium signals in previously inaccessible parts of astrocytes, including fine processes.